Pengembangan Media Pembelajaran Macromedia Flash Pada Mata Pelajaran Bahasa Indonesia Untuk Meningkatkan Kemampuan Berpikir Kritis Pada Siswa Sekolah Dasar - Faridatul Lian Maharani; Alfi Laila; Rian Damariswara (Jayapangus Press, 2023)
In the process of learning Indonesian, which actually teaches students to be able to think critically, in practice there are obstacles. Learning models that are not accompanied by media that will later make students interested and interested have not been able to maximize the evaluation of learning that has been achieved by students because it makes students lazy and bored in participating in lessons. Developing learning media using Macromedia Flash is a solution that researchers offer based on the needs analysis obtained. The purpose of this research is to be able to develop media for learning on the basis of Macromedia Flash that is applicable, practical and effective in improving students' critical thinking skills. The method in research uses the R&D method with ADDIE (investigation or analysis, design, development, implementation and evaluation or results). In this study, the subjects were 10 students at SDN Lirboyo 1 in a limited trial, and 24 students in class IV-A and 24 students in class IV-B at SDN Lirboyo II in a large-scale trial. The results of this study prove that media for learning in development scores 94.26% for validity, 87.70 for effectiveness and 95.09% for practicality. Based on these results, the researcher concluded that the learning media based on Macromedia Flash which was developed for learning Indonesian was valid, very practical and effective in improving students' skills in critical thinking.